2011
DOI: 10.1534/genetics.111.129270
|View full text |Cite
|
Sign up to set email alerts
|

RIC8 Is a Guanine-Nucleotide Exchange Factor for Gα Subunits That Regulates Growth and Development in Neurospora crassa

Abstract: Heterotrimeric (abg) G proteins are crucial components of eukaryotic signal transduction pathways. G-protein-coupled receptors (GPCRs) act as guanine nucleotide exchange factors (GEFs) for Ga subunits. Recently, facilitated GDP/GTP exchange by non-GPCR GEFs, such as RIC8, has emerged as an important mechanism for Ga regulation in animals. RIC8 is present in animals and filamentous fungi, such as the model eukaryote Neurospora crassa, but is absent from the genomes of baker's yeast and plants. In Neurospora, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 47 publications
8
55
0
1
Order By: Relevance
“…Expression of some GPCRs and G-protein subunits, especially gpr-1 and gna-3, increased after 48 h. A perithecial defect was observed for both ⌬bek-1 and ⌬gpr-1 strains (66), and abnormal perithecia with a large propotion of nonviable ascospores were found in ⌬gna-3 strains (67). Genetic tests suggest that RIC8 activates GNA-1 and GNA-3, but not GNA-2, and positively regulates the cAMP pathway in vegetative growth of N. crassa (68). In our study, expression of ric8, cr-1, gna-2, and gpr-6 was highly correlated.…”
Section: Figsupporting
confidence: 54%
“…Expression of some GPCRs and G-protein subunits, especially gpr-1 and gna-3, increased after 48 h. A perithecial defect was observed for both ⌬bek-1 and ⌬gpr-1 strains (66), and abnormal perithecia with a large propotion of nonviable ascospores were found in ⌬gna-3 strains (67). Genetic tests suggest that RIC8 activates GNA-1 and GNA-3, but not GNA-2, and positively regulates the cAMP pathway in vegetative growth of N. crassa (68). In our study, expression of ric8, cr-1, gna-2, and gpr-6 was highly correlated.…”
Section: Figsupporting
confidence: 54%
“…In this scenario, the recently discovered cytosolic guanine nucleotide exchange factor (GEF) RIC8 may function to load GTP on the remaining free G␣ proteins. We have shown that RIC8 binds to and regulates GDP/GTP exchange on GNA-1 and GNA-3 in N. crassa (57).…”
Section: Figmentioning
confidence: 91%
“…The membranes for Western analysis were probed using previously described primary antibodies for GNA-1, GNA-2, and GNB-1 at a final dilution of 1:1,000 (3,22,34,57,60). A previously described GNA-3 antibody (see Fig.…”
Section: Strains and Media N Crassa Strains Used In The Experimentsmentioning
confidence: 99%
“…In addition to the membrane-localized GPCRs, cytoplasmic nonreceptor GEFs, such as N. crassa RIC-8 (635), have recently been identified which bind to the G-protein and accelerate guaninenucleotide exchange. In M. oryzae, MoRic8 was shown to interact with and positively regulate MagB (636), and in N. crassa RIC-8 exhibited GEF activity toward the GNA-1 and GNA-3 G␣ proteins (635). Another protein with GEF activity, Arr4p/Get3p, has been described in S. cerevisiae.…”
Section: The Heterotrimeric G-protein Pathwaymentioning
confidence: 99%